Composite Material for Morphing Wing Skin Application – A Numerical Analysis - Wong, Xin Yi; Subramaniyan, S Kanna (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Aircraft design tends to overall performance and weight reduction in order to withstand the aerodynamic loads in different flight conditions. The new technology of morphing wing is to alter the wing geometry to adapt the desirable flight conditions. This study is to conduct a structural analysis for the morphing wing model by using the carbon fiber reinforced polymer (CFRP) on the flexible skin and compare the mechanical properties with Al 2014-T6 for the morphing wing model. The NACA 4415 airfoil is selected for morphing wing model. Hence, the design of morphing wing model is done by the SolidWorks software and the simulation is completed by using the ABAQUS software. The Abaqus/Explicit is used in this finite element analysis. The materials selected in the simulation is Al 2014-T6, T300/QY8911, T800/M21 and M55J/epoxy. The Al 2014-T6 is adopted for the inner structure and the CFRP composite laminates is adopted for the flexible skin. The body force is applied on the model from 1000N to 100kN with different CFRP laminates for flexible skin. From the stress-strain diagram obtained, the result shown that M55J/epoxy has the highest stiffness among the CFRP composite laminates. When comparing with the Al 2014-T6 that applied on the flexible skin, the M55J/epoxy shown the high stiffness-to-weight ratio compared to the mechanical properties of Al 2014-T6 in the stress-strain diagram. The most suitable material for the morphing wing model in this study is the high strength CFRP of M55J/epoxy for the flexible skin in order to reduce the overall weight of an aircraft with high performance during flight.